High-index faceted Pt-Ru alloy concave nanocubes with enhancing ethanol and CO electro-oxidation. (10th November 2021) - Wei, Lu; Liu, Feng; Jiang, Xin; Yang, Yu-Han; Sheng, Tian; Xu, Qing-Qiang; Zhao, Xin-Sheng; Fan, You-Jun
Abstract: High-index faceted Pt-based alloys are the promising electrocatalysts for ethanol oxidation due to their high-index facets (HIFs) structure, alloying electronic effect, and bi-functional mechanism. However, the controllable synthesis of Pt-based alloys enclosed by HIFs remains a challenge as the high surface energy, distinct standard reduction potential and atom sizes between different metals. In the present work, we propose a shape- and composition-controlled synthesis of Pt-Ru alloy concave nanocubes with high-index 510 facets via combining deep eutectic solvent (DES) with electrochemical square-wave potential. Compared with the monometallic Pt concave nanocubes and quasi-spherical Pt-Ru alloys, the as-synthesized concave cubic Pt-Ru alloys exhibit an excellent electro-oxidation performance of ethanol and CO due to the high density of low-coordinated Pt step sites (HIFs structure) and the unique electronic effect of Pt-Ru (alloying structure). Density functional theory (DFT) calculations reveal that OH* formation from water dissociation on Pt-Ru surface is apparently the rate determining step. The present of Ru on Pt(510) surface is capable to promote the OH* adsorption and then enhance the ethanol electro-oxidation reactivity and CO-resistance ability. Graphical abstract: Image, graphical abstract